2003
DOI: 10.1089/104454603322724887
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Comorbidity and Dysfunction in Clinically Referred Preschool and School-Age Children with Bipolar Disorder

Abstract: These results suggest that clinically referred preschoolers with BPD share with school-age children with BPD high rates of comorbid psychopathology and impaired functioning. Follow-up of these clinically referred preschoolers with BPD evaluating the stability of their diagnoses, treatment response, and their long-term outcome is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 58 publications
4
53
1
Order By: Relevance
“…IN CHILDREN AND ADOLESCENTS, bipolar disorder (BD) is one of the most debilitating psychiatric illnesses, often resulting in academic and social difficulties, hospitalization, and/ or suicidality (Wilens et al 2003;Dickstein et al 2005). However, questions remain regarding the diagnosis of pediatric BD, because it has been suggested that mania in youths may present with chronic irritability rather than an episodic mood disturbance (Carlson et al 1998;Leibenluft et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…IN CHILDREN AND ADOLESCENTS, bipolar disorder (BD) is one of the most debilitating psychiatric illnesses, often resulting in academic and social difficulties, hospitalization, and/ or suicidality (Wilens et al 2003;Dickstein et al 2005). However, questions remain regarding the diagnosis of pediatric BD, because it has been suggested that mania in youths may present with chronic irritability rather than an episodic mood disturbance (Carlson et al 1998;Leibenluft et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies of children with ODD demonstrate an association between irritability and negative affect, which encompasses temper outbursts, and risk for later depressive or anxiety disorders (Stringaris and Goodman 2009a,b;Burke et al 2010;Rowe et al 2010). Conversely, some investigators argue that severe outbursts are the primary manifestation of mania in children, thus justifying the diagnosis of bipolar disorder, even in very young children (Wozniak et al 1995;Wilens et al 2003). This diagnostic practice has likely contributed to the 40-fold increase in bipolar diagnoses in children since the late 1990s (Moreno et al 2007;Carlson and Glovinsky 2009).…”
mentioning
confidence: 99%
“…Many studies indicate that pediatric bipolar disorder causes significant emotional, academic, and social impairment in preschool, prepubertal, and adolescent youth Geller et al 2000a;Geller et al 2000b;Wilens et al 2003a;Craney and Geller 2003;Pavuluri et al 2005;Axelson et al 2006;Kowatch and DelBello 2006;Danielyan et al 2007;Goldstein et al 2009). Studies across many sites document the utility of pharmacotherapy treatment for pediatric bipolar disorder (Kowatch et al 2000;Delbello et al 2002b;Kowatch et al 2003;Biederman et al 2005b;Biederman et al 2005c;Findling et al 2005;Biederman et al 2007a;Biederman et al 2007b;DelBello et al 2006;Findling et al 2006).…”
mentioning
confidence: 99%